Treatment and energy valorisation of an agro-industrial effluent in upflow anaerobic sludge reactor (UASB) - Martins, Ramiro (2018)
The accelerated growth of the population brings with it an increase in the generation of agro-industrial effluents. The inadequate discharge of these effluents significantly affects the quality of water resources. In this way, it becomes important to invest in treatment processes for agro-industrial effluents, particularly low-cost ones. In this context, the present study includes the design and construction of an UASB reactor and optimization of the anaerobic digestion treatment of the raw effluent from sweet chestnut production in the agro-industrial company Sortegel. The efficiency of the system was evaluated through the determination / monitoring of oxygen chemical oxygen demand (COD), biochemical oxygen demand (BOD5), total suspended solids (TSS), biogas production rate and quality (% methane). The reactor was fed for 25 weeks and operated under mesophilic conditions (temperature 30-40 °C). Different values were tested for the hydraulic retention time (HRT) and volumetric flow rate (VF): 0.66 days (VF=1509 L.m-3.d-1); 1.33 days (VF=755 L.m-3.d-1); 2.41 d days (VF=415 L.m-3.d-1). The average COD removal efficiency reached values of 69%, 82% and 75%, respectively, and simultaneously the associated BOD5 removal efficiency was 84%, 91% and 70%. As regards TSS, removal values were 78%, 94% and 63%. In addition, high methane production rates were obtained, between 2500 and 4800 L CH4.kg-1 COD removed d-1. For all the hydraulic retention times tested, high concentrations of methane in the biogas were recorded: 66-75%, 70% and 75% for HRT of 0.66, 1.33 and 2.41 days, respectively.